Risk factors for postoperative complications in patients on maintenance hemodialysis who undergo abdominal surgery - Tomoaki Ito; Hiroshi Maekawa; Mutsumi Sakurada; Hajime Orita; Tomoyuki Kushida; Koji Senuma; Koichi Sato (Asian Journal of Surgery, 2016)
Background/Objective: Patients on hemodialysis (HD) who undergo abdominal surgery for gastrointestinal disease are at increased risk of postoperative complications. In this study, we retrospectively investigated the predictors of postoperative complications among such patients. Methods: The study group comprised 36 HD patients who underwent abdominal surgery for gastrointestinal disease between 2003 and 2012. The clinicopathological factors of the patients who did and did not suffer postoperative complications were compared. Results: The overall morbidity and mortality rates were 39% (14/36) and 14% (5/36), respectively. Physical status according to the American Society of Anesthesiologists (ASA) classification (p = 0.0203) and intraoperative blood loss (p = 0.0013) were found to differ significantly between the groups. Conclusion: The morbidity and mortality rates of HD patients who underwent abdominal surgery for gastrointestinal disease were high. Physical status according to the ASA classification and intraoperative blood loss were found to be associated with postoperative complications. Therefore, patients with comorbidities, such as heart disease and diabetes mellitus, have to be treated appropriately before surgery. In addition, it is important that surgeons perform operations carefully and avoid excessive blood loss.